Studi analisis kesulitan siswa dalam menyelesaikan soal cerita aljabar ditinjau dari level kemampuan siswa - Lilis Haniah; Eka Senjayawati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to analyze the difficulties of SMPN 02 Cililin students in solving algebra word problems in terms of students' ability levels. By understanding students' ability levels, educators can identify difficulties faced by students and develop appropriate teaching strategies to increase their understanding. This study uses a qualitative and descriptive research strategy by analyzing the difficulties experienced by students using the instruments provided. The research subjects taken were class VII students of SMPN 02 Cililin with a total of 20 students. The results of the analysis show variations in the level of students' ability to solve algebra story problems. Students with high abilities are able to correctly identify relevant variables, model mathematical relationships correctly, and reach accurate solutions. Students with moderate abilities can usually understand basic algebraic concepts, but they still need to improve their mathematical modeling and problem solving skills. Students with low abilities often have difficulty understanding basic algebraic concepts and applying them in the context of word problems.